Interpersonal Communication Patterns of Teachers Autism Children (Quantitative Descriptive Study At Medan Islamic Education Park School) - All Rizky Ramadhan (Journal Analytica Islamica, 2023)
This research is entitled Interpersonal Communication Patterns of Teachers towards Autistic Children (Descriptive Study at Medan Islamic Education Park School). The aim of the research is Interpersonal Communication Patterns for Autistic Children, because Teachers have an important role in the development of autistic children, as well as what approach the Teacher takes during the learning process because Autistic Children are very poor in communicating and interacting with the environment. The theories used in this research are interpersonal communication, teachers towards autistic children, self-disclosure theory. The method used in this research is a descriptive, quantitative method, namely describing or depicting research results systematically, factually and accurately regarding the facts and characteristics of a certain population. This research is to describe or describe the data that has been collected and then analyzed. The population in this study were 25 teachers at the Medan Islamic Education Park school. Data collection was carried out directly in the field (field research), namely by distributing questionnaires and using non-probability sampling techniques using purposive sampling according to Arikunto, by taking 100% of the total population of 25 teachers and to determine respondents the Proportional Staratifed Random Sampling technique was used. The research results show that interpersonal communication is very open. All teachers stated that they were open to all autistic children and the good relationships built by teachers with autistic children were also driven by each teacher's personality. This personality can be seen from the teacher's patience when providing teaching materials to autistic children who behave inappropriately in receiving the learning they convey Penelitian ini berjudul Pola Komunikasi Antarpersonal Guru Terhadap Anak Autis (Studi Deskriptif di Sekolah Taman Pendidikan Islam Medan). Tujuan dari penelitian adalah Pola Komunikasi Antarpribadi terhadap Anak Autis, karena Guru memiliki peranan penting terhadap perkembangan anak autis, serta secara pendekatan yang bagaimana dilakukan Guru disaat proses pembelajaranm karena Anak Autis tersebut sangat kurang dalam berkomunikasi maupun berinteraksi dengan lingkungan. Teori yang digunakan pada penelitian ini adalah komunikasim komunikasi Antarpribadi, Guru terhadap Anak Autis, Teori Self Disclosure. Metode yang digunakan dalam penelitian ini adalah metode deskriptif, kuantitatif yaitu menggambarkan atau melukiskan hasil penelitian secara sistematis, factual dan akurat mengenai fakta dan sifat populasi tertentu. Penelitian ini bersifat menggambarkan atau mendeskripsikan data yang telah terkumpul kemudian dianalisa. Populasi pada penelitian ini adalah Guru-Guru disekolah Taman Pendidikan Islam Medan berjumlah 25 orang. Pengumpulan data dilakukan langsung di lapangan (field research), yaitu dengan menyebarkan kuesioner dan menggunakan teknik penarikan sample nonprobability sampling dengan cara purposive sampling menurut arikunto, dengan cara mengambil 100% dari jumlah populasi sebanyak 25 Guru dan untuk menentukan responden digunakanlah teknik Propotional Staratifed Random Sampling. Hasil Penelitian menunjukkan bahwa komunikasi antarpribadi dengan sangat terbuka. Seluruh Guru menyatakan bahwasannya mereka terbuka kepada siapa saja anak autis dan hubungan baik yang dibangun oleh para guru dengan anak-anak autis juga didorong oleh pribadi masing-masing guru. Kepribadian tersebut dilihat dari kesabaran guru ketika memberikan bahan ajaran kepada anak-anak autis yang berprilaku kurang wajar dalam menerima pembelajaran yang mereka sampaikan.